Trust-Based Work-Time and Product Improvements: Evidence from Firm Level Data - Olivier Godart; Holger Görg; Aoife Hanley (Institute for the Study of Labor (IZA), 2014)
We explore whether the introduction of trust based working hours is related to the subsequent innovation performance of firms. Employing a panel data set of over 5,000 German establishments, we implement a propensity score matching approach where we only consider firms that did not use trust based work contracts initially. Our results show that firms which adopt such contracts tend to be between 11 to 14 percent more likely to improve products. These results hold when we control for another form of flexible time work arrangements, namely working time accounts. Thus, the positive relationship between the adoption of trust based working hours and innovation seems to be driven by the degree of control and self-management over working days, rather than by merely allowing time flexibility.
Keywords: M54; M12; 330; trust based work time; innovation; firm performance